Effects of different water and fertilizer treatments on the matrix properties and plant growth of tailings waste - Yanchen Li; Yang Yang; Jialin He; Shan Guo; Xuejing An; Yan Li; Rui Guo; Yipeng Lin; Ruipeng Zhang (Scientific Reports)
Abstract Vegetation ecological restoration technology is widely regarded as an environmentally sustainable and green technology for the remediation of mineral waste. The appropriate ratio of amendments can improve the substrate environment for plant growth and increase the efficiency of ecological restoration. Herbs and shrubs are preferred for vegetation restoration in abandoned mines because of their rapid establishment and easy management. This study probed into their improvement effects on abandoned mine tailings from aspects such as plant growth and nutrient content. Based on this, the trail explored the impacts of different ratios of quarry waste matrix on different plant growth and the physical and chemical properties of the quarry matrix. The original soil, without fertilizer and with 45% water treatment, was taken as the control (CK), while the experimental group comprised of composite soil with different ratios of original soil and slag, combined with various water and nitrogen fertilizer treatments. Pennisetum alopecuroides (L.) Spreng, Campsis grandiflora (Thunb.) Schum, Setaria glauca (L.) Beauv, Periploca sepium Bunge, and mugwort (Artemisia argyi Levl. Et Vant.) were planted, respectively, in the control and experimental groups. After a 30-day period of nitrogen fertilizer and water treatment, an analysis was conducted to evaluate the physicochemical properties and growth status of the tailing matrix for different treatments. The results demonstrated that the M7 treatment significantly promoted the growth of mugwort, whereas the M2 treatment stimulated the growth of Campsis grandiflora (Thunb.) Schum. Additionally, the M3 treatment proved to be advantageous for enhancing the growth of Setaria glauca (L.) Beauv, Pennisetum alopecuroides (L.) Spreng, and Periploca sepium Bunge. The soil matrix pH of Pennisetum alopecuroides (L.) Spreng, Campsis grandiflora (Thunb.) Schum, Setaria glauca (L.) Beauv, Periploca sepium Bunge, and mugwort is all above 7.5, while macronutrient elements including TK, AK, TN, AN, TP, and AP exhibit varying degrees of enhancement. PCA analysis disclosed that there were significant disparities in substrate properties and plant growth properties among treatments for Pennisetum alopecuroides (L.) Spreng, Campsis grandiflora (Thunb.) Schum, Setaria glauca (L.) Beauv, Periploca sepium Bunge, and mugwort (P < 0.05). The correlation network and structural equation analysis revealed a significant positive correlation between the water and fertilizer matrix and soil AN and TN (P < 0.05). Additionally, TK exhibited a positive correlation with the growth status of all five plant species. Moreover, the water and fertilizer substrate displayed a positive association with the growth status of Pennisetum alopecuroides (L.) Spreng, Setaria glauca (L.) Beauv, Periploca sepium Bunge, as well as mugwort; however, it showed a negative correlation with the growth status of Campsis grandiflora (Thunb.) Schum.